Analisis Gaya Belajar Siswa Dan Gaya Mengajar Guru Bahasa Inggris Di Sma Se Kabupaten Tulang Bawang - Hery Yufrizal (LINGUISTIKA, 2010)
The study aims at finding out the influence of students learning styles and teachers teaching style on the students English achievement at senior high schools of Tulang Bawang Regency in Lampung Province. The number students recruited as the sample for the study was 1038 and the number of teachers recruited as the sample was 70 teachers. Two sets of questionnaires each for learning style and teaching style were given. Students learning styles are categorized into: a) con-ununicative, b) concrete, authority-oriented, d) analytic, and e). undecided. Teachers styles are categorized into:a) expert, b) formal authority, c) personal model, d) facilitator, and e) delegator.The results show that there is no significant influence of students learning styles on their achievement of English subject, while teaching style has a significant effect on the students achievement. There is a tendency that students at senior high school in Tulang Bawang prefer teachers who apply formal authority style than teachers with other styles, but students who got better achievements are those were taught by teachers with expert and facilitator styles.Penelitian ini bertujuan untuk menemukan pengaruh gaya belajar siswa dan gaya mengajar guru terhadap prestasi Bahasa Inggris siswa SMA di Kabupaten Tulang Bawang. Jumlah siswa yang direkrut sebagai sample adalah 1038 siswa sedanagkan guru yang terlibatberjumlah 70 prang. Dua perangkat kuesioner masing-masingZ~untuk gaya belajar siswa dan gaya mengajar guru diberikan kepada sample penelitian. Gaya belajarsiswa dikategorikan sebagai: a) siswa komunikatif, b) siswa kongkrit, e) siswa berorientasi kekuasaan, d). siswa analitik, dan e) siswa campuran. Gaya guru dikategorikan sebagai: a) guru expert, b) guru formal authority, c) guru personal model, d) guru .facilitator, dan e) gui-it delegator.Hasil penelitian rnelILl uj ukkan bahwa tidak ada pengaruh yang signi I ikan antara gaya belajar siswa dengan prestasi belajar Bahasa Inggris mereka, sedangkan gaya mengajar guru berpengaruh secara signifikan terhadap prestasi belajar Bahasa Inggris siswa. Ada kecenderungan siswa SMA di Kabupaten Tulang BawangTulangleiluii menyukai guru yang memiliki gaya formal authority daripada gaya lainnya, tetapi siswa yang prestasi Bahasa Inggrisnya balk adalah mereka yang diajar oleh guru expert danfilcilaitator.